Implementation of Breakout Strategy and Adaptive Risk Management in an Expert Advisor with Optimized Bollinger Bands and RSI Parameters on MetaTrader 5 - Nasution, Mutiara Akbar; Rahman, Haikal (Economic: Journal Economic and Business, 2025)
The development of automated trading systems in forex markets has increased the demand for adaptive strategies based on technical indicators. This study aims to develop and evaluate an Expert Advisor (EA) utilizing a breakout strategy integrated with Bollinger Bands and Relative Strength Index (RSI) indicators, as well as adaptive risk management, on the MetaTrader 5 platform. A Research and Development (R&D) approach using the Prototyping model was employed to iteratively design and refine the EA. The system was evaluated through three stages: backtesting, parameter optimization, and real-time testing on three major currency pairs—EUR/USD, GBP/USD, and USD/JPY. Parameter optimization using the Fast Genetic Based Algorithm led to improved performance across all pairs, with significant enhancements in drawdown reduction and profit factor. One-month real-time testing demonstrated that the EA maintained a profit factor above 1 and a drawdown below 1% for EUR/USD and GBP/USD. The findings indicate that integrating a breakout strategy with technical indicator optimization and adaptive risk management significantly enhances the effectiveness of automated trading systems. This research contributes to both academic literature and practical applications in the development of algorithmic trading systems based on technical indicators.